Text and context in functional linguistics - Ghadessy, Mohsen, 1935- (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory, 1999)
This text aims to examine the nature of text and context, using theoretical models based in the framework of Systemic Functional Linguistics (SFL).